Comparative Evaluation Of Microsurgical And Conventional Open Flap Debridement꞉ A Randomized Controlled Trial - Latha, Kristipati; Rani, Moka Leela; Suresh, Peddengatagari; Divya, Kathi; Bhargavi, Kellapattu; Rana, Riya R (Journal of Neonatal Surgery, 2025)
Aim: To compare the clinical outcomes of microsurgical and conventional open flap debridement in patients with generalized periodontitis stage III, grade B. Materials and methods: A total of 40 patients with the age range of 21- 50 years were taken into the study from the Out-Patient Section of the Department of Periodontics, Government Dental College and Hospital, Kadapa, India. A split-mouth study design was employed. Each patient was given a brief description of the intended surgical procedure and was required to sign an informed consent paper. Control sites consist of 40 sites treated by conventional open flap debridement. Test sites comprised 40 sites treated by microsurgical open flap debridement. Results: There were no statistically significant differences among the groups with respect to Probing Pocket Depth, Clinical Attachment Level, and Gingival Recession, but there was a reduction within the groups from baseline to 9 months except in Gingival Recession. The intergroup comparison of the Visual Analogue Scale of pain and the Early Wound Healing Index showed significant results in the Test group than in the Control group 1 week after the operation. Conclusion: An improvement was observed in all the clinical parameters except Gingival Recession in both the groups from baseline to 9 months with no statistical significance in the between the groups. However, the intergroup comparison revealed a reduction in pain and better healing in the test group compared to the control group.